Covariation in width and depth in bedrock rivers. Issue 6 (1st March 2022) - Wright, Morgan; Venditti, Jeremy G.; Li, Tingan; Hurson, Max; Chartrand, Shawn; Rennie, Colin; Church, Michael
Abstract: The width and depth of rivers are generally inversely related. For a given discharge, wider rivers tend to be shallower than narrower rivers, which are correspondingly deeper. This is particularly true in bedrock and mixed bedrock–alluvial channels, where deep pools occur downstream of lateral constrictions, downstream of which the channel becomes wider and shallower. However, covariation of width and depth in bedrock and mixed bedrock–alluvial rivers has never been explored due to the lack of field measurements. Here we present a 375 km survey of width and depth measurements in the Fraser Canyon, British Columbia, which alternates irregularly among alluvial (no bedrock exposed on either bank), bedrock‐constrained (bedrock exposed on one bank), and bedrock‐bound (bedrock exposed on both banks) sections. We find that bedrock‐bound reaches have the deepest and narrowest sections, followed by bedrock‐constrained reaches and alluvial reaches, which feature the shallowest and widest sections of channel. There is an inverse relation between width and depth for all the channels, with alluvial channels having the highest correlation between these two variables, and thus the greatest covariance. We further explore the relation between width and depth and the downstream hydraulic geometry of 42 individual bedrock‐bound canyons. There is an inverse relation between canyon width and depth, with substantial variation within individual canyons. The downstream hydraulic geometry for these bedrock‐bound canyons does not follow that typical of alluvial channels; depth is the only variable that adjusts substantially as a response to increasing discharge and upstream basin area. Abstract : Width and depth covary differently based on channel type, with varying degree of covariation for individual canyons. Consequently, the downstream hydraulic geometry of fully bedrock‐bound channels (banks and bed) does not conform to alluvial scaling, with depth being the only variable that adjusts substantially to account for changes in discharge. Landscape evolution models that assume alluvial channel scaling for bedrock reaches need to consider that the local morphology may differ substantially from that assumed in the models.